A Functional Screening Identifies a New Organic Selenium Compound Targeting Cancer Stem Cells: Role of c‐Myc Transcription Activity Inhibition in Liver Cancer. Issue 22 (2nd June 2022) - Zhou, Jun‐Nian; Zhang, Biao; Wang, Hai‐Yang; Wang, Dong‐Xing; Zhang, Ming‐Ming; Zhang, Min; Wang, Xiao‐Kui; Fan, Shi‐Yong; Xu, Ying‐Chen; Zeng, Quan; Jia, Ya‐Li; Xi, Jia‐Fei; et al.
Abstract: Cancer stem cells (CSCs) are reported to play essential roles in chemoresistance and metastasis. Pathways regulating CSC self‐renewal and proliferation, such as Hedgehog, Notch, Wnt/ β ‐catenin, TGF‐ β, and Myc, may be potential therapeutic targets. Here, a functional screening from the focused library with 365 compounds is performed by a step‐by‐step strategy. Among these candidate molecules, phenyl‐2‐pyrimidinyl ketone 4‐allyl‐3‐amino selenourea (CU27) is chosen for further identification because it proves to be the most effective compound over others on CSC inhibition. Through ingenuity pathway analysis, it is shown CU27 may inhibit CSC through a well‐known stemness‐related transcription factor c‐Myc. Gene set enrichment analysis, dual‐luciferase reporter assays, expression levels of typical c‐Myc targets, molecular docking, surface plasmon resonance, immunoprecipitation, and chromatin immunoprecipitation are conducted. These results together suggest CU27 binds c‐Myc bHLH/LZ domains, inhibits c‐Myc‐Max complex formation, and prevents its occupancy on target gene promoters. In mouse models, CU27 significantly sensitizes sorafenib‐resistant tumor to sorafenib, reduces the primary tumor size, and inhibits CSC generation, showing a dramatic anti‐metastasis potential. Taken together, CU27 exerts inhibitory effects on CSC and CSC‐associated traits in hepatocellular carcinoma (HCC) via c‐Myc transcription activity inhibition. CU27 may be a promising therapeutic to treat sorafenib‐resistant HCC. Abstract : A novel organic selenium compound, phenyl‐2‐pyrimidinyl ketone 4‐allyl‐3‐amino selenourea (CU27), is developed, which can bind c‐Myc bHLH/LZ domains, block c‐Myc‐Max complex formation, and prevent its occupancy on target gene promoters in hepatocellular carcinoma (HCC) cells. These effects lead to the suppression of cancer stem cell self‐renewal, resulting in inhibition of metastasis and sorafenib resistance in HCC. CU27 may be a promising therapeutic to treat sorafenib‐resistant HCC.